Professionalism in records management practices to ensure good governance in Malaysia: a review / Norhaida Hanim Ahmad Tajudin, Mohd Zaidi Mohd Hajazi and Nur Syufiza Ahmad Shukor - Ahmad Tajudin, Norhaida Hanim; Mohd Hajazi, Mohd Zaidi; Ahmad Shukor, Nur Syufiza (Faculty of Information Management, 2023)
Professionalism is a very important aspect in the execution of all processes and activities in records management practice. It is imperative to ensure proper management of records to curb problems such as unauthorized access, loss of information, poor handling, and non-compliance with established procedures that are recurrent in records management practice due to lack of professionalism among records managers. The objective of this paper is therefore to examine the elements of professionalism required in records management in Malaysia. Various articles in reputable online databases were searched using the keywords “professionalism,” “records management practices” and “good governance.” The study found that there are aspects of professionalism to be considered in records management, with the most important elements, namely accountability, integrity, and honesty, to ensure the smooth running of records management. The study concluded that professionalism is an important component of the professional requirements of records management as it is an important aspect of good governance. Professionalism, therefore, involves not only knowledge and skills, but also attitude and behaviour.